291 Injury rates and mechanisms of injury in female high school rugby. (3rd March 2020) - Shill, Isla; Black, Amanda M; Sick, Stacy; Kolstad, Ash; Palacios-Derflingher, Luz; Schneider, Kathryn; Hagel, Brent E; Emery, Carolyn
Abstract : Background: In Canada, unlike many countries, youth rugby players often have their first exposure to the sport in high school (ages 15–16). There are few studies examining injuries in female high school rugby union. Objective: To describe injury rates and mechanisms among females participating in high school rugby union. Design: Prospective cohort study. Setting: Rugby pitches (Calgary, Canada). Participants: Female high school rugby players (ages 15–18) participating in 2018 (7 teams, n=214) and 2019 (7 teams, n=207) seasons. Assessment of risk factors: Mechanism of injury was recorded by team designates on an electronic injury report form, validated by a certified athletic therapist. Main outcome measurements: Training and match injuries were identified by a team designate or study therapist if the player 1) required medical attention, 2) was unable to complete the session, and/or 3) unable to participate in activity for ≥ one day. Results: There were 71 match injuries [33.1 per 100 athlete-seasons (exact 95%CI, 26.9–40.0)] and 39 training injuries [18.2 per 100 athlete-seasons (exact 95%CI, 13.3–24.1)] in the 2018 season, and 84 match injuries [40.5 per 100 athlete-seasons (exact 95%CI, 33.8–47.6)] and 46 training injuries [22.2 per 100 athlete-seasons (exact 95%CI, 16.8–28.5)] in the 2019 season. Match injuries most commonly occurred while tackling [n=62(40%), 14.7 injuries per 100 athlete-seasons], being tackled [n=47(30%), 11.1 injuries per 100 athlete-seasons], and during a ruck/maul [n=12(8%), 2.9 injuries per athlete-seasons]. Training injuries most commonly occurred while tackling [n=17(20%), 4.0 injuries per 100 athlete-seasons], being tackled [n=17(20%), 4.0 injuries per 100 athlete-seasons], and during non-contact [n=13(15%), 3.1 injuries per 100 athlete-seasons]. Conclusions: Tackling was identified as the most common mechanism of injury among female high school rugby players, with the highest rates in the active tackler during matches. Safe tackling interventions are an ideal primary prevention target to reduce the risk of injury within this population.